Identification of Opportunities for Utilizing E-Modules with a Problem Based Learning Approach to Facilitate Learning in Vocational High Schools - Habibi, Muchtar; Sunardi; Sudiyanto (Jurnal Edutech Undiksha, 2022)
The demands of the times to integrate ICT into the learning process can be realized through the development of digital learning media. This study aims to analyses students' needs for types of digital learning media in the hope that they will suit their needs and be able to solve problems that occur in the field. This study uses a mixed methods approach with an explanatory model. Quantitative data collection techniques by giving questionnaires to 64 Vocational High School students. Qualitative data were obtained from interviews and observations of learning activities with the research subject, namely the Subject Teacher. Quantitative data were analyzed through descriptive analysis with percentages, and qualitative data were analyzed using the Bogdan and Biklen models. The results of the overall needs analysis show that teachers still use conventional and non-ICT-based learning media. Teachers, through the results of interviews, stated that if they needed innovative learning media in e-module format for classroom learning, this was supported by the responses of students who helped the presence of PBL-based e-modules for classroom learning. Based on the results of identifying needs, an innovative digital learning media is needed in the e-module format that can be used for both classical and independent learning in the hope of supporting the improvement of students' critical thinking skills.